Multiple endocrinopathies (growth hormone deficiency, autoimmune hypothyroidism and diabetes mellitus) in Kearns-Sayre syndrome - A. Berio; A. Piazzi (PAGEPress Publications, 2013)
Kearns-Sayre syndrome is characterized by onset before 20 years, chronic progressive external opthalmoplegia, pigmentary retinal degeneration, and ataxia (and/or hearth block, and/or high protein content in the cerebrospinal fluid) in the presence of mtDNA rearrangements. Multiple endocrine dysfunction associated with this syndrome was rarely reported. In this paper, the Authors report on a female patient with Kearns-Sayre syndrome with large heteroplasmic mtDNA deletion, absence of cytochrome c oxidase in many muscle fibers, partial GH deficiency, hypothyroidism and subsequently insulin dependent diabetes mellitus (IDDM). Anti-thyroid peroxidase and antithyreoglobulin antibodies were present in high titer in serum while anti-islet cell antibodies were absent. The patient developed thyroiditis with Hashimoto encephalopathy. The presence of GH deficiency, autoimmune thyroiditis with hypothyroidism and IDDM distinguishes this case from others and confirms the association of Kearns-Sayre syndrome with multiple endocrine dysfunction. Hashimoto encephalopathy and anti-thyroideal antibodies suggest that in this patient, predisposed by a genetic factor (a mitochondrial deletion) anti-thyroideal antibodies may have contributed to the hypothyroidism and, by interfering with cerebral mitochondrial function, may have caused the encephalopathy. GH deficiency and IDDM can be attributed to oxidative phosphorylation deficiency but the autoimmunity may also have played a role in the production of glandular insufficiencies. It seems important to search for endocrine autoimmunity in every case of KSS.